Mechatronics : an introduction - Bishop, Robert H., 1957- (Taylor & Francis, 2006)
Mechatronics has evolved into a way of life in engineering practice, and it pervades virtually every aspect of the modern world. In chapters drawn from the bestselling and now standard engineering reference, The Mechatronics Handbook, this book introduces the vibrant field of mechatronics and its key elements: physical system modeling; sensors and actuators; signals and systems; computers and logic systems; and software and data acquisition. These chapters, written by leading academics and practitioners, were carefully selected and organized to provide an accessible, general outline of the subject ideal for non-specialists.